Analysis of projects for economic growth : an operational system for their formulation, evaluation, and implementation - Solomon, Morris J. (New York ; London : Praeger Publishers, 1970)
This is a guide for the formulation and evaluation of projects with full regard to the political, social, and economic values of society. Its origins are to be found in an Agency for International Development advisory mission to Turkey. It covers: project analysis; decision making and implementation; how a project is prepared; time-phasing and discounting; shaping the project; economic yardsticks for proposed projects; case study of a proposed chemical project; some complicating factors; some notes on procedures; choosing the location; sensitivity analysis; agricultural projects; social overhead projects; exploring alternatives; and organising for economic development.
Includes bibliographical references.
lje 04/10/2018
Loans
Keywords: Economic development; Project management